Molecular Characterisation of Urothelial Bladder Cancer: Will it Improve Patient Care? - Erben, P.; Hartmann, Arndt; Bolenz, C. (Aktuelle Urologie, 2015)
Urothelial bladder cancer is characterised by high recurrence and progression rates despite multimodal treatment. Only slight improvements have been achieved during the last decades. The current histopathological classification and clinical risk stratification tools are inaccurate. Hence, a better understanding of the tumour biology is essential for the improvement of patient care. The molecular characterisation of bladder cancer may be translated into useful diagnostic and predictive biomarkers. Many potential therapeutic targets have been identified such as FGFR3 (Fibroblast growth factor receptor 3), HER2 (human epidermal growth factor receptor 2) and PD1/PDL1 (programmed cell death-1). They need validation in clinical trials. We now review the molecular biology of urothelial bladder carcinoma and discuss clinical applications of biomarkers and targeted therapies.
EVALuna2:6754